Efficient Production System Resource Exploration Considering Product/ion Requirements - Kathrein, Lukas; Meixner, Kristof; Winkler, Dietmar; Luder, Arndt; Biffl, Stefan (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2019)
For the design of a Production System (PS), engineers have to select production resources that address the associated product and production process, i.e., product/ion, requirements. The dependencies between product, process, and resource (PPR) provide the foundation for mapping properties of the product and process to skills of production resources, which may be represented as attributes in resource catalogue tables. However, the production resources are represented in resource catalogues by heterogeneous sets of attributes that make it challenging to efficiently find a set of well-fitting resources. In this paper, we present challenges and quality criteria that we identified with domain experts at a large Production Systems Engineering (PSE) company. We focus on use cases that explore and select resources from large resource catalogues. We introduce a data model to organize these resource catalogues in the solution space based on PPR knowledge. We propose a method for efficiently exploring the resource solution space regarding PPR requirements. In a conceptual feasibility study, domain experts rated the quality of the method based on a conceptual prototype. The domain experts found the approach feasible and useful to efficiently document decisions on resource selection.